Viabilidade do aproveitamento de resíduo de estação de tratamento de água (ETA) na confecção de concretos - Ramirez, Kleber Gomes (2015)
The aim of this study is to evaluate the influence of replacing natural sand by different levels of Water Treatment Plant Sludge (WTP sludge) in the production of environmentally friendly concrete. The experiment included the collection and characterization of raw materials, the concrete dosing study produced with different sludge replacement levels of Wet Sludge (WS) and Calcined Sludge (CS) and the evaluation of the produced mixtures with regards the technical, economic and environmental aspect. The sludge samples used in the study were collected from the Tamandua ETA, located in Foz do Iguaçu, Paraná, in three different periods during the year 2014. In the dosage of study, WS (in natura) was substituted by natural sand in the levels of 0, 5, 7 and 10% in concrete with water/cement ratio (w/c) of 0.45, 0.55 and 0.65 and CS (temperature of 900 °C) in levels of 0, 5, 10 and 20% in mixtures with w/c of 0.55, evaluating the properties in the fresh state (workability) and in the hardened state (resistance to axial compression, tensile strength, elastic modulus, water absorption and leaching). From the results obtained it was found that the addition of CS up to 20% resulted in an increase in the mechanical properties of concrete, therefore it can be used in structural concrete, provided that durability studies are carried out. With regards WS, its addition significantly reduces the strength of concrete and is suitable, from a technical point of view, a replacement level up to 5% for applications in concrete, provided that not structural. From an economic point of view, in comparison to the reference concrete, concrete produced with WS resulted in lower production cost while concrete with CS the cost was higher. By thermogravimetric analysis, the sludge may be calcined at lower temperatures (300 to 500 °C), leading to energy saving in the heat treatment process, resulting in an improvement in the economic and environmental factor in the application of the calcinated sludge in the production of concrete. With regards the environmental viability, the results demonstrated that the levels of concentration of the substances analyzed in the leaching test meet the maximum allowed limit, ensuring environmental and human health. The sustainability of sludge use in concrete is confirmed by the reduction in the extraction of natural resources, contributing mainly to the decreas of sludge release in water bodies, and upon satisfying the requirements of the management and environmental legislation system. Further studies should be conducted to assess the effect of replacing sand for higher levels of sludge, analyzing the economic and environmental viability linked to the calcination process.